Mafhūm Ahl al-Sunnah wa al-Jamā’ah ‘Inda Jam’īyah Nahḍah al-‘Ulamā’ - Mohammad Tolchah Hasan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2005)
this article deals with one of the basic pillars of traditionalist Islam in Indoneisa, ahlussunah waljama'ah (Ar. ahl al-sunnah wa al-jama'ah, meaning people of the sunnah and the [orthodox] community). it was first advocated in Indonesia by the leading 'ulama of the pesantrens, and then appeared as a key religious principle for Nahdlatul Ulama (NU), an institution of 'ulama in Indonesia established in 1926.DOI: 10.15408/sdi.v12i1.648